Passive ultrasonic irrigation provides less debris after post space preparation - Girotto, Aline Carvalho [UNESP]; Bravo, Giovana Righetti [UNESP]; Escalante-Otarola, Wilfredo Gustavo [UNESP]; Belizario, Laurie Garcia [UNESP]; Kuga, Milton Carlos [UNESP] (My University, 2019)
Objective: The present study evaluated the residues (de-bris) incidence in dentin fiber post space submitted to ir-rigation protocols using distilled water (DW), 2.5% sodium hypochlorite (HS), 2.5 % sodium hypochlorite and 17% EDTA (HSE), or 2.5% sodium hypochlorite energized by passive ultrasonic irrigation (HSUS). Methods: Forty bo-vine incisors root canals with standardized root length (17.0 mm) were obturated using single cone technique and epoxy resin sealer. After 7 days, the fiber post space was prepared using # 1 and # 2 Largo burs, and DC2 (White Post; FGM). The specimens were randomly divided into four groups (n= 10), according to the irrigation protocol: AD; HS, HSE or HSUS. After 48 hours, the roots were sectioned. Cervical and apical segment images were obtained using scanning electron microscopy (500X). Scores were assessed accord-ing to debris presence. Results: In cervical segment, HSE and HSUS presented debris incidence lower than DW and HS (P <0.05). DW and HS or HSE and HSUS were similar to each other (P > 0.05). Conclusions: HSUS provided the lower debris incidence in dentin surface of the fiber post space (P < 0.05).
Keywords: Dental Restoration; Dentin; Endodontics; Permanent.; Sodium Hypochlorite